2020
DOI: 10.1186/s13244-020-00910-6
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences of radiographers in Ireland during the COVID-19 crisis

Abstract: Background Imaging is crucial for assessing the severity and progression of COVID-19. Radiographers are amongst the first-line health professionals that may be exposed to infected persons. This work describes the early experience of radiographers in Ireland to the impact of COVID-19 using two electronic surveys distributed 6 weeks apart. Results were analysed using descriptive statistics and thematic analysis. Results A total of 370 responded to the first survey and 276 the second, with all six Irish health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 11 publications
4
45
0
1
Order By: Relevance
“…Participants talked extensively about the emotional and psychological toll of the virus on their loved ones, their patients/clients, and on them personally. This finding corroborates other research that shows the negative impact of working on the frontline in terms of mental health, wellbeing, burnout, lowered resilience and posttraumatic stress (Ali et al, 2020;Foley et al, 2020;Kannampallil et al, 2020;Ruiz & Gibson, 2020;. In the present research, some participants expressed a lowered sense of optimism which, as previous research has shown, is a key predictor of emotional distress and less effective coping strategies (David et al, 2006).…”
Section: Managing Their Distresssupporting
confidence: 92%
“…Participants talked extensively about the emotional and psychological toll of the virus on their loved ones, their patients/clients, and on them personally. This finding corroborates other research that shows the negative impact of working on the frontline in terms of mental health, wellbeing, burnout, lowered resilience and posttraumatic stress (Ali et al, 2020;Foley et al, 2020;Kannampallil et al, 2020;Ruiz & Gibson, 2020;. In the present research, some participants expressed a lowered sense of optimism which, as previous research has shown, is a key predictor of emotional distress and less effective coping strategies (David et al, 2006).…”
Section: Managing Their Distresssupporting
confidence: 92%
“…It was reported that frontline HCPs like radiographers, who often had to take on the role of caring directly for patients with COVID-19 were at a higher-level risk of having severe mental health symptoms than those in secondary roles[ 76 ]. They had to work with the constant changing protocols with some reported to have inadvertent exposure to COVID-19 positive patients without suitable PPE — a result of poor communication[ 77 ]. Moreover, some radiographers experienced burnout as they were subjected to 12-hour shifts in order to meet the service needs and for team segregation[ 78 ].…”
Section: Challenges In the Provision Of Medical Imaging Service During Covid-19mentioning
confidence: 99%
“…As the pandemic continues to spread globally, clear communication with radiographers is necessary to ensure infection control[ 103 ]. If radiographers are communicated promptly regarding the health of the patient to be scanned, appropriate PPE can be worn in advance — avoiding repetition of miscommunication incidents that led to radiographers in Ireland[ 77 ] being exposed to COVID-19 positive patients without donning appropriate PPE. Moreover, such clear communication is crucial in ensuring that radiographers comply and perform self-monitoring for symptoms when exposed to positive cases[ 101 ].…”
Section: Strategies To Optimize Medical Imaging Service Delivery During Covid-19mentioning
confidence: 99%
“…7e14 Diagnostic imaging modalities employed for direct COVID-19 patient management (general X-ray [CXR] including mobile systems) and computed tomography (CT) were perceived to have been under increased procedural pressure while other elective/non-urgent diagnostic and screening services were paused in some settings globally. 7,9,10,15,16 Staff were reassigned to modalities with anticipated increase in pressure such as CXR and CT. 7,9,14 Worldwide, reports and experiences indicate that there has been extensive re-organisation within radiology and radiotherapy departments to conform with the COVID-19 guidelines to effectively manage the anticipated pandemic-related workload increases while keeping workflows safe. 1,16e19 In some settings, additional radiography practice modifications were required to reduce crossinfection, such as X-raying through room windows 20,72,73 with both the digital image receiver/cassette and mobile X-ray machine secured with layers of polythene sheets.…”
Section: Introductionmentioning
confidence: 99%